2020
DOI: 10.1007/s42729-020-00187-0
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Ash Application on the Carbon Mineralization and Microbial Biomass Carbon of Reclaimed Mining Soils

Abstract: Ash resulting from biomass energy resource utilization contains a wide range of metal oxides and hydroxides, which may influence the capacity of the ash to be used as a soil amelioration material. This study aimed to assess the effects of different ashes on changes in soil carbon (C) mineralization and soil microbial biomass carbon (MBC) in reclaimed mining soils (RMSs). Different levels (0, 25, 50, and 75 Mg ha −1) of three ashes (rice husk, oil palm shell, and coal fly ash) were applied to 10-year RMS for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 71 publications
2
9
0
Order By: Relevance
“…Ash application to soils serve as liming agents which makes it suitable for use in acidic soil. For the amendment combination with ash, both soil types showed similarities to previous studies [41] in which PMD+A resulted in increased DHA and SMB-C after the experiment. The combination of pig manure digestate with ash can be assumed to have a convincing effect by increasing the pH of the acidic soil, indirectly in uencing soil C mineralization and SMB-C through changes in the activity of soil microorganisms.…”
Section: Changes In Soil Microbial Activities From the Soil Amendmentsupporting
confidence: 80%
“…Ash application to soils serve as liming agents which makes it suitable for use in acidic soil. For the amendment combination with ash, both soil types showed similarities to previous studies [41] in which PMD+A resulted in increased DHA and SMB-C after the experiment. The combination of pig manure digestate with ash can be assumed to have a convincing effect by increasing the pH of the acidic soil, indirectly in uencing soil C mineralization and SMB-C through changes in the activity of soil microorganisms.…”
Section: Changes In Soil Microbial Activities From the Soil Amendmentsupporting
confidence: 80%
“…Coal fly ash application to both soils increased the contents of exchangeable Ca and Mg, FeD, FeO, and AlO, in which these increases were in line with the amounts of added coal fly ash (Table 2). Coal fly ash encompassed quite high amounts of Ca, Mg, Al and Fe (Saidy et al, 2020); thus, the addition of coal fly ash raised the amounts of exchangeable Ca and Mg, FeD, FeO, and AlO of the amended soils. Results of this study are in agreement with the previous studies that reported the improvement of soil chemical characteristics following coal fly ash application (Pandey and Singh, 2010;Riehl et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Samples of coal fly ash were transferred to the laboratory, air-dried for several days, then sieved to obtain coal fly ash with a diameter of <2.0 mm prior to being used for the experiments. Coal fly ash properties for this research have been reported by Saidy et al (2020).…”
Section: Sampling Of Soil and Coal Fly Ashmentioning
confidence: 99%
“…Organo−mineral associations, , which are formed from the reaction of organic matter with multivalent cations such as Ca 2+ and Fe 3+ , are organic materials that are resistant to microbial decomposition, and thereby increasing soil organic carbon stabilization [14,15]. Coal fly-ash (CFA) which is produced from the process of using coal as an energy source, generally contains high amounts of multivalent cations such as Ca, Mg, and Fe [16,17], so it has the potential to be used as a soil ameliorant. Although many studies have been conducted on the effect of CFA application on changes in peat properties, information on the effect of CFA application on changes in GHG production of peatlands is still not comprehensively available.…”
Section: Introductionmentioning
confidence: 99%